(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
As living beings, our reliance on plants and animals for sustenance is crucial. However, the available food resources cannot sustain the global population for extended periods, as only 29% of the Earth’s land is suitable for sustaining the entire ecosystem. If we didn’t have plant-eating bacteria or locusts, we might have enough resources to last for years. This is where my project, Plant Disease Detection and Recognition, comes into play. The main objective of this project is to identify and diagnose the diseases affecting plants, as well as determine the most effective treatments. By utilizing this system, we can obtain accurate information about the specific diseases afflicting plants. Additionally, we can identify the appropriate medications for eradicating these diseases completely. Plant diseases pose significant threats to the well-being of plants and trees, making it vital to detect them early in order to take appropriate measures. Understanding the type of disease before administering treatment is crucial. With a 92% accuracy rate, our system enables us to work on plants effectively, thereby extending their lifespan. After undergoing multiple tests, this initiative has emerged as a promising boon for humankind. Farmers, who serve as the backbone of nations, play a crucial role in our survival. Ensuring that they receive fair prices for their yields is paramount, and our system will play a significant role in achieving this. By supporting agricultural sustainability and promoting healthier crops, we can create a positive impact on food production and contribute to the overall well-being of society.